Advances in Versatile Nanoscale Catalyst for the Reductive Catalytic Fractionation of Lignin. Issue 11 (29th April 2021) - Zhang, Haichuan; Fu, Shiyu; Du, Xu; Deng, Yulin
Abstract: In the past five years, biomass‐derived biofuels and biochemicals were widely studied both in academia and industry as promising alternatives to petroleum. In this Review, the latest progress of the synthesis and fabrication of porous nanocatalysts that are used in catalytic transformations involving hydrogenolysis of lignin is reviewed in terms of their textural properties, catalytic activities, and stabilities. A particular emphasis is made with regard to the catalyst design for the hydrogenolysis of lignin and/or lignin model compounds. Furthermore, the effects of different supports on the lignin hydrogenolysis/hydrogenation are discussed in detail. Finally, the challenges and future opportunities of lignin hydrogenolysis over nanomaterial‐supported catalysts are also presented. Abstract : One big sweep : A comprehensive Review is provided about advances in versatile nanoscale catalysts for the reductive catalytic fractionation of lignin, which includes carbon‐supported catalysts, transition metal carbide catalysts, solid acid catalysts, porous metal oxides, metal‐organic framework materials, and metal sulfides for the catalytic hydrogenolysis of lignin models, isolated lignin and native lignin. Effects of supports on reactivity and stability are also briefly introduced.